2016
DOI: 10.1080/15384101.2016.1188239
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of monocarboxylate transporter expression in oral cavity tumors

Abstract: Overexpression of MCT1/4, CD147, GLUT1 and CAIX, supports previous findings of metabolic reprograming in OCC, warranting future studies to explore the hyper-glycolytic phenotype of these tumors. Importantly, MCT expression revealed to have a prognostic value in OCC survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 66 publications
4
39
0
Order By: Relevance
“…Understanding the role of these transporters in tumours will clarify their contribution to tumour metabolism and the malignant phenotype. Recent efforts have been made to identify the prognostic significance of MCT1 [ 14 , 15 , 21 , 23 , 24 , 34 ] and MCT4 (reviewed by [ 36 ]) in different tumour types, however none have studied their role in EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the role of these transporters in tumours will clarify their contribution to tumour metabolism and the malignant phenotype. Recent efforts have been made to identify the prognostic significance of MCT1 [ 14 , 15 , 21 , 23 , 24 , 34 ] and MCT4 (reviewed by [ 36 ]) in different tumour types, however none have studied their role in EC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MCT4 (efflux of lactate) and MCT1 (both influx and efflux of lactate) are among the most important regulators of intracellular pH homeostasis in tumours and other high glycolytic tissues [ 10 , 11 ]. Upregulation of MCTs has been shown in many malignancies including colorectal [ 12 , 13 ], cervix [ 14 ], breast [ 15 , 16 ], prostate [ 17 ], central nervous system [ 18 , 19 ], soft tissue [ 20 ], gastrointestinal [ 21 , 22 ], oral cavity [ 23 ], urothelial [ 24 ] and lung carcinomas [ 25 ] and high expression is associated with poor prognosis. Both MCT1 and 4 require association with the ancillary protein CD147 (also known as EMMPRIN or Basigin) for plasma membrane expression and activity [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MCT family consists of fourteen members [29,30]; MCT4 is the only member with H + -dependent transporters of monocarboxylic acids [31,32]. Increasing reports show that expression of MCT4 has also been linked to poor prognosis in several cancers [33,34]. Malignant tumors overexpress MCT4, characteristic of metastatic cancer in association with HIF-1α upregulation [35,36].…”
mentioning
confidence: 99%
“…For that reason, the role of MCTs in several cancer types, including expression analysis in human cancer tissues have been widely explored in the past years (for an extensive review see [16]). MCT1 and MCT4 are upregulated in tumour cells when compared to adjacent normal tissue in a variety of human malignancies including lung [17], breast [18], head and neck [19], renal [20], brain [21], adrenal [22], melanomas [23], pancreatic [24], colorectal [25], ovarian [26], bladder [27] and cervix [28]. Interestingly, in liver and prostate cancer, MCT1 appears downregulated, while MCT4 is upregulated [29,30].…”
Section: Expression and Prognostic Value Of Mctsmentioning
confidence: 99%
“…Diverse immunohistochemical studies have reported CAIX to be expressed in several cancers, including malignancies of the breast [167,168], colon/rectum, head and neck [19,169], lung [170], brain [171], bladder [172], ovarian [173], and kidney [166] (for review see [174]). Importantly, its expression is scarce in normal human tissues, being only detected in the gastrointestinal tract [175].…”
Section: Expression and Prognostic Value Of Casmentioning
confidence: 99%